New Science Literacy: Problems and Difficulties of Formation - Margolis A.A (Moscow State University of Psychology and Education, 2022)
In a pandemic, science literacy is transformed from a subject of sociological research into a question of the survival of society itself. attitude of various groups and individuals to vaccination shows the real state of science literacy and reveals significant problems in its formation. The article examines the main stages in the development of the concept of natural science (science) literacy and the importance of critical science literacy in a stream containing conflicting scientific information and expert opinions. The article demonstrates the ineffectiveness of formation strategies without specially organized work on the development of initial pre-science ideas in children and adults.